2021
DOI: 10.1161/circresaha.120.316819
|View full text |Cite
|
Sign up to set email alerts
|

RYR2 Channel Inhibition Is the Principal Mechanism of Flecainide Action in CPVT

Abstract: Rationale: The class Ic antiarrhythmic drug flecainide prevents ventricular tachyarrhythmia in patients with catecholaminergic polymorphic ventricular tachycardia (CPVT), a disease caused by hyperactive RyR2 (cardiac ryanodine receptor) mediated calcium (Ca) release. Although flecainide inhibits single RyR2 channels in vitro, reports have claimed that RyR2 inhibition by flecainide is not relevant for its mechanism of antiarrhythmic action and concluded that sodium channel block alone is responsible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 46 publications
0
71
0
Order By: Relevance
“…At the cellular level, this could be reflected in differing reports of its in vivo actions in both suppressing Ca 2+ waves in intact and permeabilized myocytes, while increasing Ca 2+ spark frequency [28]. In contrast, in intact hearts from a homozygotic CPVT mouse model exhibiting compromised Nav1.5 function, flecainide, despite being a Nav1.5 blocker, mediated anti-arrhythmic effects likely via the inhibition of RyR2-mediated Ca 2+ release [6,7,16,33]. This indirect, RyR2-mediated effect may be the basis for the recent use of flecainide monotherapy in human CPVT, although here individuals are usually heterozygotic and thus flecainide could be acting on both WT and mutant RyR2 [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…At the cellular level, this could be reflected in differing reports of its in vivo actions in both suppressing Ca 2+ waves in intact and permeabilized myocytes, while increasing Ca 2+ spark frequency [28]. In contrast, in intact hearts from a homozygotic CPVT mouse model exhibiting compromised Nav1.5 function, flecainide, despite being a Nav1.5 blocker, mediated anti-arrhythmic effects likely via the inhibition of RyR2-mediated Ca 2+ release [6,7,16,33]. This indirect, RyR2-mediated effect may be the basis for the recent use of flecainide monotherapy in human CPVT, although here individuals are usually heterozygotic and thus flecainide could be acting on both WT and mutant RyR2 [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has been provided that flecainide is effective in reducing DCR in cells harboring the RyR2 R4496C +/− mutation, but this effect could be masked by experimental conditions such as Ca overload [93]. On the other hand, more convincing evidence comes from a recent study that employed a synthesized analog of flecainide with reduced inhibition on RyR2 activity but unaltered inhibition on Na channel [94]. This analog failed to reduce DCR at cellular level and arrhythmia burden in vivo, indicating that flecainide acts through inhibition of RyR2 activity.…”
Section: Na Channel Blockers and Flecainidementioning
confidence: 99%
“…Up until now, classic antiarrhythmic drugs' main mechanism known to prevent arrhythmias does not include the mitochondrial-SR interconnection. However, they have effects on either of these organelles (Sugiyama et al, 1985;Sano et al, 1990;Deng and Zhang, 1993;Tsutsumi et al, 2001;Afanas'ev et al, 2002;Ugdyzhekova et al, 2005;Wang et al, 2007;Bannister et al, 2015;Kryshtal et al, 2020). Flecainide can inhibit RyR2 opening, although its relevance in preventing arrhythmias is still controversial (Bannister et al, 2015;Kryshtal et al, 2020).…”
Section: Final Remarksmentioning
confidence: 99%
“…However, they have effects on either of these organelles (Sugiyama et al, 1985;Sano et al, 1990;Deng and Zhang, 1993;Tsutsumi et al, 2001;Afanas'ev et al, 2002;Ugdyzhekova et al, 2005;Wang et al, 2007;Bannister et al, 2015;Kryshtal et al, 2020). Flecainide can inhibit RyR2 opening, although its relevance in preventing arrhythmias is still controversial (Bannister et al, 2015;Kryshtal et al, 2020). Lidocaine might inhibit mitoK ATP channels, as shown in isolated cardiomyocytes utilizing a mitochondrial redox state reporter as a surrogate for mitoK ATP opening (Tsutsumi et al, 2001), and prevents mitochondrial Ca 2+ overload in a model of closed-chest VF and resuscitation (Wang et al, 2007), but the widely reported mechanism of action of Lidocaine is prolonging the inactivation of the fast voltage-gated Na + channels, inhibiting spontaneous depolarization (Sheu and Lederer, 1985).…”
Section: Final Remarksmentioning
confidence: 99%